2019
DOI: 10.1097/mao.0000000000002389
|View full text |Cite
|
Sign up to set email alerts
|

Early Magnetic Resonance Imaging for Patients With Idiopathic Sudden Sensorineural Hearing Loss in an Emergency Setting

Abstract: Objective: The role of magnetic resonance (MR) imaging in idiopathic sudden sensorineural hearing loss (ISSHL) is controversial due to the inhomogeneity of clinical and MR protocols. The aim of this work is to relate early MR findings obtained immediately after the admission, with the clinical presentation, the audiological findings, and the outcomes of treatment. Study Design: Prospective observational study. Setting: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…As a systematic review and meta-analysis of Lammers et al [2019] mentioned, knowledge of the time between the onset of SSNHL and MR was essential for proper interpretation of imaging findings since signal intensity of blood in the CSF changes due to the dissociation of hemoglobin. However, our results showed that the difference in the period from SSNHL onset to MR examination between MR+ and MR− groups was not statistically significant, similar to the results of previous studies [Lee et al, 2016;Wang et al, 2019;Conte et al, 2019;Min et al, 2020]. In our opinion, the reason may be that membranous labyrinthine hemorrhage was less common (21%) compared with labyrinthitis (79%) overall [Lammers et al, 2019], and only 1 case in our study.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…As a systematic review and meta-analysis of Lammers et al [2019] mentioned, knowledge of the time between the onset of SSNHL and MR was essential for proper interpretation of imaging findings since signal intensity of blood in the CSF changes due to the dissociation of hemoglobin. However, our results showed that the difference in the period from SSNHL onset to MR examination between MR+ and MR− groups was not statistically significant, similar to the results of previous studies [Lee et al, 2016;Wang et al, 2019;Conte et al, 2019;Min et al, 2020]. In our opinion, the reason may be that membranous labyrinthine hemorrhage was less common (21%) compared with labyrinthitis (79%) overall [Lammers et al, 2019], and only 1 case in our study.…”
Section: Discussionsupporting
confidence: 86%
“…In our study, 30.1% (28/93) patients with unilateral SSNHL had labyrinthine signal abnormalities, the positive rate was nearly the same as the range of previous studies (25.8%-64.5%). The large variability may be mainly due to the different MR protocols and different objects (bilateral or unilateral SSNHL) [Ryu et al, 2011;Berrettini et al, 2013;Lee et al, 2016;Liao et al, 2016;Byun et al, 2019;Conte et al, 2019]. It is worth noting that the cochlear lesions accounted for 90.6% (29/32) of the positive cases found by our MR protocol.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Vestibular and cochlear PE are also important parameters in the grading method proposed by Bernaerts ( 13 ). A different study showed that both T1-weighted and FLAIR MRI were negative in patients with idiopathic SSHL, but high signal on postcontrast delayed 3D-FLAIR MRI often indicated BLB disruption ( 24 ). However, in the present study, the presence of vestibular PE was noted in 9 patients, and all of these patients had isolated PE without the presence of EH.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, quantitative synthetic MRI has been reported to better detect high signal intensity in the affected inner ear compared to the 3D-FLAIR sequences [ 36 ]. MRI sequences with contrast enhancement evaluation and 4 h delayed acquisitions demonstrated higher precision in defining the site and extension of the inner ear lesions, especially for fluid compartments [ 37 ]. An MRI-based volumetric analysis of inner ear fluids has been also recently proposed in order to indirectly evaluate endolymphatic hydrops [ 38 ].…”
Section: Future Directionsmentioning
confidence: 99%